The new argonauts : regional advantage in a global economy - Saxenian, AnnaLee; Harvard University Press (Cambridge, Mass. : Harvard University Press, 2006)
Extends geographer's pioneering research into the dynamics of competition in Silicon Valley. This book brings a fresh perspective to the way that technology entrepreneurs build regional advantage in order to compete in global markets. It is useful for scholars, policymakers and business leaders.
-- Surprising success -- Learning the Silicon Valley system -- Creating cross-regional communities -- Taiwan as silicon sibling -- Taiwan as partner and parent -- Manufacturing in Mainland China -- IT enclaves in India -- The Argonaut advantage -- App. A: Immigrant professional and networking associations, Silicon Valley -- App. B: Survey results : immigrant professionals in Silicon Valley.
Includes bibliographical references (pages [353]-407) and index.
Keywords: High technology industries -- Developing countries; Immigrants -- California -- Santa Clara Valley (Santa Clara County); Cooperative industrial research -- California -- Santa Clara Valley (Santa Clara County)